New immunosuppressive agents in pediatric transplantation (Clinics, 2014)
Immunosuppressive therapy in pediatrics continues to evolve. Over the past decade, newer immunosuppressive agents have been introduced into adult and pediatric transplant patients with the goal of improving patient and allograft survival. Unfortunately, large-scale randomized clinical trials are not commonly performed in children. The purpose of this review is to discuss the newer immunosuppressive agents available for induction therapy, maintenance immunosuppression, and the treatment of rejection.